2015
DOI: 10.4172/2167-0420.1000290
|View full text |Cite
|
Sign up to set email alerts
|

Why Unmet Need for Family Planning Remains High in Bangladesh: A Community Level Analysis

Abstract: Background: Improving reproductive health (RH) is widely recognized as a key component of social and economic development. Interaction of different factors such as individual, household and community level covariates plays an important role in determining the level of unmet need for family planning. Objectives: The objective of the study is to examine the association between individual, household and community level covariates with the level of unmet need for family planning in Bangladesh. Methodology: For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 22 publications
8
19
2
Order By: Relevance
“…In another study, the principal barrier to use contraceptive was fear of side effect in (46.1%) cases 14 Pradhan et al showed that educated women had desire for fewer children than their less educated counterparts because of incompatibility between formal sector employment and child care. This study also revealed parity decline with increased level of education 16 . Contraceptive use rate also varies according to number of living children.…”
Section: Discussionsupporting
confidence: 61%
“…In another study, the principal barrier to use contraceptive was fear of side effect in (46.1%) cases 14 Pradhan et al showed that educated women had desire for fewer children than their less educated counterparts because of incompatibility between formal sector employment and child care. This study also revealed parity decline with increased level of education 16 . Contraceptive use rate also varies according to number of living children.…”
Section: Discussionsupporting
confidence: 61%
“…Unmet need for contraception was determined by individual-level factors ((age, age of marriage education and occupation status of the mother) [16][17][18][19], husband factors (occupation and educational status of husband) [20][21][22], household factor (wealth)) [23] and community-level factor (place of residence, region, community-level of education and media exposure) [24][25][26]. Unmet need for family planning is an important concept that is largely used for reproductive health advocacy, designing family planning policies and the monitoring/evaluation of implemented programs especially Sustainable Developmental Goals (SDGs) and Growth and Transformation Plan two (GTPІІ) [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Unmet need for contraception was determined by individual-level factors ((age, age of marriage education and occupation status of the mother) [16][17][18][19], husband factors (occupation and educational status of husband) [20][21][22], household factor (wealth)) [23] and community-level factor (place of 4 residence, region, community-level of education and media exposure) [24][25][26]. Unmet need for family planning is an important concept that is largely used for reproductive health advocacy, designing family planning policies and the monitoring/evaluation of implemented programs especially Sustainable Developmental Goals (SDGs) and Growth and Transformation Plan two (GTPІІ) [27,28].…”
Section: Introductionmentioning
confidence: 99%